Big Five personality traits in the occurrence and repetition of nonsuicidal self-injury among adolescents: The mediating effects of depressive symptoms. (October 2016) - You, Jianing; Lin, Min-Pei; Xu, Sian; Hu, Wei-Hsuan
Abstract: This study used zero-inflated Poisson regression to examine the relations of the Big Five personality traits to the occurrence and repetition of nonsuicidal self-injury (NSSI), as well as the mediating effect of depression in these relationships. A number of 2874 Chinese high school students in Taiwan completed questionnaires assessing NSSI, the Big Five personality traits, and depression. Neuroticism was positively associated with both the occurrence and repetition of NSSI. Extraversion and agreeableness were negatively related to the occurrence and repetition of NSSI, respectively. Depression mediated all these relationships. This study suggests that neuroticism may act as a risk factor for NSSI. Extraversion and agreeableness may act as protective factors. Clinical implications of these findings are discussed. Highlights: Neuroticism was positively associated with both the occurrence and repetition of NSSI. Extraversion was negatively associated with the occurrence of NSSI. Agreeableness was negatively associated with the repetition of NSSI. Depression mediated all these relationships.